The impact of knowledge management and organizational learning promotion in small and medium enterprises on the implementation of industry 4.0 and competitiveness - Chun-Hung Cheng; Meng-Hua Li; Bau-Jen Tang; Yea-Rong Cheng (Administrative Sciences, 2024)
The transformation and upgrading of small- and medium-sized enterprises (SMEs) need to align with global industrial development trends and can further assist SMEs in sustainable operation. In recent years, major industrial countries, such as Germany, China, and the United States, have promoted policies like Industry 4.0 or advanced manufacturing as part of their national manufacturing transformation strategies. In contrast, how SMEs follow these global industrial development trends and effectively apply new technologies hinges on internal knowledge management and organizational learning. To achieve the benefits of new technology implementation, enterprises must establish an effective knowledge management and organizational learning mechanism and promotion practices. The Taiwanese government has also adopted Industry 4.0 as an essential tool for assisting the transformation and upgrading of SMEs. Therefore, this study surveyed 129 SMEs in the Taiwanese metal industry, using a one-way ANOVA, Pearson correlation analysis, and simple regression analysis to explore the impact of the internal promotion of knowledge management and organizational learning on the introduction of Industry 4.0 and the enhancement in competitiveness. The results of this study indicate that the promotion of knowledge management and organizational learning contributes to the effective adoption of Industry 4.0 and the enhancement in competitiveness, showing significant correlations between these factors. Thus, the findings can serve as a reference for other partner countries.
Keywords: 350; Industry 4.0; knowledge management; organizational learning; SMEs; sustainable operation